MANFAAT PEMBELAJARAN FINGER PAINTING BAGI ANAK USIA DINI - Suryawan, I Gde; Ariputra, I Putu Suyasa; Sindu, Ida Bagus Komang (Institut Agama Hindu Negeri Gde Pudja Mataram, 2022)
Education is closely related to the process of organizing to fully achieve educational goals. Using appropriate learning methods in the learning process is one of the keys to the success of the learning process. Good learning methods need to be adapted to the age of students, because there are many learning techniques in learning methods that educators can apply to achieve what they want to achieve. Learning to draw with practice with finger painting technique is a form of adapting teaching and learning techniques used by TK Kusawa Hanagiri by taking into account the age level of students. Based on this, the writer then carried out qualitative descriptive activities and finger painting which was supported by data analysis using the triangulation stage using data collection techniques in the form of observations, interviews, and library searches. The following are the results of the analysis of the mean of finger painting learning in Kusawakagiri Kindergarten. Based on these results, there is some debate. 1) Finger painting develops students' imagination. That is, the child's imagination, which is mainly influenced by the environment, is acquired in the process of observing the child and in himself. Through this process, the head that is built will be able to foster children's creative thinking and develop their intelligence, enabling them to think critically. 2) Finger painting fosters student creativity. In short, learning finger painting allows children to create new conditions based on existing data, information and elements (creativity). 3) Painting with fingers as a source of inspiration, painting with fingers as a source of implied inspiration is a detailed practice process for students.